Vitreoretinal Disorders (Current Practices in Ophthalmology,, 2018)
This book discusses the newest trends, concepts, and advancements in the management of vitreo-retinal conditions. The field of retina is rapidly changing, with new advances ranging from stem cell therapy, gene therapy and editing, new drug targets, novel delivery systems, and innovative technologies in advanced ocular imaging and surgical techniques. The goal is to provide a way to update practitioners and trainees on how the field of retina is changing. Areas of focus include new technologies, particularly in ocular imaging and vitreo-retinal surgery, major new clinical trials, particularly those that are shifting practice patterns or addressing novel therapies, and novel research that is altering the classification and diagnosis of retinal conditions, as well as management strategies and prognostic predictors for vitreo-retinal diseases. This volume is essential reading for generalist and specialist ophthalmologists and useful for residents and fellows training in various subspecialties.